2018
DOI: 10.1515/cclm-2018-0128
|View full text |Cite
|
Sign up to set email alerts
|

Point-of-care creatinine testing for kidney function measurement prior to contrast-enhanced diagnostic imaging: evaluation of the performance of three systems for clinical utility

Abstract: The screening of patients at risk of CI-AKI may be feasible with PoC technology. However, in this study, it was identified that the analyser concordance with the laboratory reference varies. It is proposed that further research exploring PoC implementation in imaging department pathways is needed.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
24
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
4
3

Relationship

1
6

Authors

Journals

citations
Cited by 35 publications
(29 citation statements)
references
References 24 publications
5
24
0
Order By: Relevance
“…The concordance of the study PoC device with the laboratory gold standard is consistent with other evaluations [16,17,23,24,34] and provides reassurance around the test results. Following appropriate training radiographers and support staff were able to undertake sample testing with a relatively low failure rate, which appears to reduce with experience.…”
Section: Accepted Manuscriptsupporting
confidence: 81%
See 3 more Smart Citations
“…The concordance of the study PoC device with the laboratory gold standard is consistent with other evaluations [16,17,23,24,34] and provides reassurance around the test results. Following appropriate training radiographers and support staff were able to undertake sample testing with a relatively low failure rate, which appears to reduce with experience.…”
Section: Accepted Manuscriptsupporting
confidence: 81%
“…Following written consent, all participants completed a screening questionnaire based on previous studies [23,24,[27][28][29], as is the local standard of care. The questionnaire sought details of known kidney disease, diabetes, heart failure, hypertension, plus history of current/recent acute illness (in…”
Section: Study Proceduresmentioning
confidence: 99%
See 2 more Smart Citations
“…Studies comparing the performance of the i-STAT device to other platforms have been inconsistent. 35 , 36 , 37 , 38 One study showed that the i-STAT overestimated creatinine results by 3.88 µmol/L in comparison to the Roche enzymatic creatinine results. This overestimation occurred predominantly at higher creatinine concentrations.…”
Section: Discussionmentioning
confidence: 99%